REVOLUTION AND IDENTITY - Voropai, Tetiana S. (The Journal of V. N. Karazin Kharkiv National University, Series Philosophy. Philosophical Peripeteias, 2018)
Identity is a constant sign of social groups in peace and stability, but it is problematic in times of crisis (war, revolution, civil conflict, social crisis, etc.) when community is aware not only who he is, but also rethinking who it wants or should be. Especially when an enemy appears, or at least «the image of the enemy». Identity is the birth of a political subjectivity in a community that is geopolitically considered an object of international relations. In the literature, the cliché has already become a kind of statement about the fact that Ukraine is an object and not a subject of international relations, a change card in foreign geopolitical games. That is, the self-consciousness of the nation is worthless and does not affect anything. To refute this statement is the main purpose of this article. The objective of the article is to integrate, unbiased, objective analysis of the formation of the Ukrainian political nation, conducted from different points of view. In this regard, the article consists three parts, devoted to three different aspects of the problem: a purely geopolitical review of the works of the most well-known and influential scholars on the problem of Ukrainian-Russian relations after the revolutionary events in Ukraine and their futurological predictions; identity problems associated with the war on the Donbass; the influence of modern mass media into the formation of the ideology of the hybrid war and the hybrid world. The theoretical basis of the article is based, first of all, on the geopolitical postulates of freedom from ethical assessments and, on the contrary, the importance of geographical dates. The search and articulation of these data is the main scientific novelty of the article. In many respects, we relied on the methodology of geopolitical analysis introduced by John Friedman and Samuel Huntington, and tried to combine their positions into a coherent and holistic picture. The main conclusions of the work can be summarized in approximately these theses. Culture, not just politics and geography, matters. Identity is not a constant, it is a variable and super-complicated construct, aimed more for the future than the past. The ideology of nationalism can be both useful in the process of becoming a nation and state creation, and erroneous when it contradicts the picture of the post-modern world of the XXI century and the principles of democracy.